The State and the Economic Development of Bulgaria from the Liberation of 1878 to the Balkan Wars (1879-1912) – In Search of An Effective Policy - Dimitrov, Marko (Research Papers, 2014)
The study examined the activity of the Bulgarian state in the economic sphere and its results in the period between the liberation from Ottoman rule in 1878 and the wars that led to Bulgaria from 1912 to 1918. The main focus of the study is critical analysis and evaluation of the government economic policy and its impact on changes in agriculture and industry in the late nineteenth and early twentieth century. The author identifies the positive aspects of this policy, as well as certain weaknesses in its planning and implementation. The author evaluates the different opinions prevailing in the historiography on some key issues in the economic development of Bulgaria and the economic policy of the Bulgarian state during this period, the economic consequences of the Russo-Turkish War (1877-1878) industrial and agricultural policy after liberation, fiscal and trade policy, etc.